1976
DOI: 10.1093/ajcp/65.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomesotheliomatous Carcinoma of the Lung: A Variant of Peripheral Lung Cancer

Abstract: Six cases of primary lung cancer that closely mimic malignant pleural mesothelioma clinically and anatomically are compared with four proven cases of malignant pleural mesothelioma. Findings on roentgenograms of the chest, clinical history, and gross examination of the lung specimens are not helpful in distinguishing between these two neoplasms. Microscopic examination of the hematoxylin and eosin-stained tissues is often inconclusive. Tissues were stained with hematoxylin and eosin, PAS with and without diast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(57 citation statements)
references
References 0 publications
0
56
0
1
Order By: Relevance
“…Mucin was identified in all 6 cases described by Harwood et al (4). In all 12 PMAL cases previously reported (4, 8 -11), epithelial mucin was demonstrated in the neoplastic cells.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…Mucin was identified in all 6 cases described by Harwood et al (4). In all 12 PMAL cases previously reported (4, 8 -11), epithelial mucin was demonstrated in the neoplastic cells.…”
mentioning
confidence: 66%
“…The average survival of 12 PMAL cases previously reported (4,(8)(9)(10)(11)) was 6 months after admission. Koss et al (12) reported that all PMAL patients dies with/of tumor, with a mean survival of 4.7 months for those reported in the medical literature and of 7 months for those in the Armed Forces Institute of Pathology files.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…(2) The malignant meso thelioma mimics other carcinomas from small cell carcinomas to adenocarcinomas metastasizing to the pleura [2][3][4][5], However, malignant cells in pleural effu sions due to carcinomatous mesothelioma may show typical morphologic features. They consist of multinucleation, optically dense cytoplasm with changing staining be havior, marginal vacuolisation, 'windows' between two adjacent cells and 'cell in cell' formation of malignant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma is seen most frequently, and primary sites include lung, breast, gastrointestinal tract, ovary, thyroid and kid ney [142], In many cases, the primary site is not deter mined during life [143,144], Some peripheral adeno carcinomas of the lung, and more rarely squamous carcinomas, spread over pleural surfaces in a manner similar to mesothelioma and it may be difficult to es tablish where in the lung such tumours have origi nated [145]. In distinguishing between secondary adenocarcinoma of the pleura and mesothelioma of epithelial type, mucus stains, immunohistochemistry and electron microscopy are all helpful (see above).…”
Section: Secondary Tumours Of the Pleuramentioning
confidence: 99%